UPAYA MENINGKATKAN HASIL BELAJAR PASSING DENGAN MENGGUNAKAN KAKI BAGIAN DALAM PERMAINAN SEPAK BOLA MELALUI PENDEKATAN BERMAIN PADA SISWA KELAS V SD NEGERI 104321 PAYA PASIR KECAMATAN TEBING SYAHBANDAR KABUPATEN SERDANG BEDAGAI T.A. TAHUN AJARAN 2017/2018 - Benhard Sinambela (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
The research location is at SD Negeri 104321 Paya Pasir, Tebing Syahbandar District, Serdang Bedagai Regency. The time of this research will be carried out in the 2017/2018 academic year in July 2017. And the subject in this classroom action research is class V SD Negeri 104321 Paya Pasir, Tebing Syahbandar District, Academic Year. 2017/2018 which amounted to 29 people. The purpose of this study was to improve the learning outcomes of passing in soccer games. Based on the data on the results of the initial passing test using the inner foot in the soccer game above, it can be seen that the student learning outcomes in learning passing using the inner foot in the soccer game are still low. Of the 31 students who were the subjects in this study, it turned out that only 13 students (41.93%) had mastery learning, while the rest, namely 18 students (58.07%) did not yet have learning mastery. The average value obtained only reached 76.29. Based on the cycle I data above, it can be seen that student learning outcomes in learning passing using the inside of the foot in soccer games have started to increase. Of the 31 students who became subjects in this study, it turned out that there were 27 students (87.10%) who had mastery learning, while 4 students (12.90%) still did not have learning mastery. The average grade obtained in the first cycle was 78.49. Based on this, it can be concluded that there was an increase in learning outcomes of passing by using the inner foot in soccer games through a play approach to fifth grade students at SD Negeri 104321 Paya Pasir, Tebing Syahbandar District, Serdang Bedagai Regency, T.A. 2017/2018 Academic Year.